2001
DOI: 10.1177/00912700122010500
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine Metabolism in Premature Infants

Abstract: Caffeine has been used frequently in the treatment and prevention of apnea of prematurity. The metabolism of caffeine depends on the activities of the hepatic enzymes that vary from one infant to another. The objective of this study was to determine the influence of postnatal age (PNA), birth weight (BW), study weight (SW), gestational age (GA), postconceptual age (PCA), and gender on the maturation of caffeine metabolism in premature infants. The caffeine base was administered orally as a loading dose of 10 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
1
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 25 publications
0
27
1
2
Order By: Relevance
“…Some of this variability could be related to the collection times, because daily variability is reported to be between 6.1% to 35.0%. 30,39 However, because the peak caffeine level is at 30 to 120 minutes, the half-life is approximately 100 hours and the dosing is every 24 hours, the differences between levels within the 12 hours before the next dose are expected to be minimal by 1 week of treatment. 15,30 In our cohort, two factors appeared to be positively associated with higher caffeine levels (≥16 μ g/mL after 1 week of treatment): older GA and Caucasian race.…”
Section: Discussionmentioning
confidence: 99%
“…Some of this variability could be related to the collection times, because daily variability is reported to be between 6.1% to 35.0%. 30,39 However, because the peak caffeine level is at 30 to 120 minutes, the half-life is approximately 100 hours and the dosing is every 24 hours, the differences between levels within the 12 hours before the next dose are expected to be minimal by 1 week of treatment. 15,30 In our cohort, two factors appeared to be positively associated with higher caffeine levels (≥16 μ g/mL after 1 week of treatment): older GA and Caucasian race.…”
Section: Discussionmentioning
confidence: 99%
“…15 The rate of metabolism of caffeine is found to be higher in female than male preterm neonates. 16 Peak plasma concentration with both oral and intravenous route is almost the same and is reached within thirty minutes to two hours. The clearance increases non-linearly with increasing post-natal age, reaching a plateau at 120 days, and volume of distribution increases linearly with increasing weight.…”
Section: Pharmacokineticsmentioning
confidence: 96%
“…Multiple serum lots were spiked with UA/X/HX at 500/10/10 M, respectively, for the test. Because of the structural similarity of X and HX to caffeine (1,3,7-trimethyl X), three major metabolites of caffeine from hydroxylation, oxidative demethylation by cytochrome P-450 1A2 and xanthine oxidase metabolism [45][46][47] were tested for possible chromatographic interference on the HPLC system. The results showed that 1-methyl-X at 30 M (approximately 30-fold the expected serum concentration) contributed as a small interference peak at the retention time of X as depicted in the overlaid chromatograms of X and 1-methyl-X in Fig.…”
Section: Selectivity Testsmentioning
confidence: 99%